Strategi Pendidik dalam Meningkatkan Kualitas Belajar Mengajar pada Pembelajaran Pendidikan Agama Islam di Era Globalisasi - Gusmita Zalianti; Maya Sari; Ahmad Sabri; Rulli Hidayatullah (Yayasan Perguruan Kampus, 2024)
Islamic religious education is very important in the current era of globalization. To improve the quality of teaching and learning in Islamic religious education learning, effective educator strategies are needed. The purpose of this study is to identify educators' strategies that can improve the quality of teaching and learning in learning Islamic religious education in the era of globalization. This research uses a qualitative research method using a descriptive approach. Data were collected through various sources such as journals, books, articles and other sources. The results showed that there are several effective educator strategies in improving the quality of teaching and learning in learning Islamic religious education in the era of globalization. In addition, educators need to apply student-centered teaching methods. In the context of learning Islam, this can be done by providing space for students to share their experiences and understanding of Islam. This approach allows students to be actively involved in learning and strengthens their understanding of religious values. Effective educator strategies in improving the quality of teaching and learning in Islamic religious education learning in the era of globalization involve the use of approaches that emphasize the global context, the utilization of information and communication technology, and the application of student-centered teaching methods